LIMBAH RANTING, DAUN, DAN BUNGA KERING SEBAGAI MATERIAL PENCIPTAAN KARYA RUSTIC WOOD SLICE - Swastika Dhesti Anggriani; Lisa Sidyawati; Abdul Rahman Prasetyo; Elvira Kurnia Ramadhani (Institut Seni Indonesia Yogyakarta, 2021)
The purpose of designing this rustic wood slice artwork with the basic material of waste branches, leaves, and dried flowers is to create new artwork and develope the skills of productive communities in Watu Gong, Malang City, East Java. This rustic wood slice is a artwork that can be used as decorative objects, used objects, and souvenirs for visitors of The Watu Gong. The method used in this study is method of craft creation which consist of 3 stages including exploration, design, and realization of actualization. The exploration phase starts from observing natural resources, such as wood, branches, leaves, and flowers which can be processed into basic materials for making rustic wood slice artwork. At the design stage, several sketches were made as an alternative design. From these alternative, one design sketch was chosen which was turned into an actual artwork. The realization or actualization stage is carried out by several processes, including preparation of tools and materials, exploration main materials and supporting materials placement, and actualization of the actual artwork. The results of this creation are 2 types of rustic wood slice artwork, namely rustic wood slice jar and rustic wood slice mirrorTujuan perancangan karya rustic wood slice dengan bahan dasar limbah ranting, daun, dan bunga kering ini adalah menciptakan karya baru dan mengembangkan keterampilan masyarakat produktif di daerah Watu Gong, Kota Malang, Jawa Timur. Karya rustic wood Slice ini merupakan salah satu karya yang dapat dijadikan sebagai benda hias, benda pakai, dan souvenir bagi pengunjung objek wisata Watu Gong yang ada di daerah ini. Metode penciptaan yang digunakan adalah metode penciptaan seni kriya yang mencakup 3 tahapan, yaitu eksplorasi, perancangan, dan pewujudan. Tahap eksplorasi dimulai dari pengamatan sumber daya alam, seperti kayu, ranting, daun, dan bunga yang dapat diolah menjadi bahan dasar pembuatan karya rustic wood slice. Pada tahap perancangan, dibuat beberapa gambar sketsa desain sebagai alternatif desain. Dari beberapa alternatif desain tersebut dipilih 1 gambar sketsa yang akan diwujudkan menjadi karya sebenarnya. Tahap pewujudan dilakukan melalui beberapa proses, yaitu persiapan alat dan bahan, eksplorasi peletakan material utama dan material pendukung, serta pewujudan karya sebenarnya. Hasil penciptaan berupa dua jenis karya rustic wood slice, yaitu toples rustic wood slice dan kaca cermin rustic wood slice.